2021
DOI: 10.3762/bjoc.17.9
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of aryl 2-bromo-2-chloro-1,1-difluoroethyl ethers through the base-mediated reaction between phenols and halothane

Abstract: An efficient and convenient method for the synthesis of structurally unique and highly functionalized aryl 2-bromo-2-chloro-1,1-difluoroethyl ethers has been developed. This approach exhibits a broad reaction scope, a simple operation and without the need of any expensive transition-metal catalyst, highly toxic or corrosive reagents. Notably, we demonstrate the potential utility of halothane for the synthesis of aryl gem-difluoroalkyl ethers containing the bromochloromethyl group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 42 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…However, the yield of 2n was 32% (Table 2, entry 13). In the case of aminophenol (3o), nucleophilic addition occurred predominantly at the phenoxide position and the product was obtained in moderate yield (Table 2, entry 14). An aryl iodide also participated in the reaction (Table 2, entry 15).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the yield of 2n was 32% (Table 2, entry 13). In the case of aminophenol (3o), nucleophilic addition occurred predominantly at the phenoxide position and the product was obtained in moderate yield (Table 2, entry 14). An aryl iodide also participated in the reaction (Table 2, entry 15).…”
Section: Resultsmentioning
confidence: 99%
“…Scheme 1: Reaction of phenol with polyfluoroalkanes. We recently reported that the reaction of halothane with various phenoxides proceeded smoothly to provide various aryl difluoroalkyl ethers (1), along with small amounts of fluoroalkenyl ethers (2), which were obtained from 1 via an E2-elimination mechanism (Scheme 1B) [14,15]. The fluoroalkenyl group in 2 is a potentially useful moiety that could participate in crosscoupling reactions for replacement of the bromine atom with an aryl or alkynyl unit [16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Phenols were found to react with hydrogen‐containing freons such as HCFC‐123 (CF 3 CHCl 2 ), HCFC‐133a (CF 3 CH 2 Cl), and HFC‐134a (CF 3 CH 2 F) by Chen et al., [57,58] and reactions with halothane were performed by Yagupol'skii et al. and Omote et al [59–61] . Chen et al.…”
Section: Electrophilic Halogenated Alkenes Produced From Freons and H...mentioning
confidence: 99%
“…and Omote et al. independently studied variations in this reaction using a series of phenols with various functionalities and found that the reaction with base‐labile esters and pyridines readily proceeds without their decomposition [58,61,63] . If the phenol contains an amino group, phenoxide attack of 26 is dominant, giving the desired product 27 because the phenoxide group is more nucleophilic than the amino group.…”
Section: Electrophilic Halogenated Alkenes Produced From Freons and H...mentioning
confidence: 99%
See 1 more Smart Citation